Development and performance evaluation of fluted pumpkin seed dehulling machine - Odewole, M. M.; Adesoye, O. A.; Oyeniyi, S. K.; Isiaka, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
A machine for dehulling fluted pumpkin seed (Telfairia occidentalis) was developed. The main objective of developing the machine was to provide a better substitute to traditional methods of dehulling the seed which contains edible oil of high medicinal and nutritional values. Traditional methods are full of drudgery, slow, injury prone and would lead to low and poor outputs in terms of quantity and quality of dehulled products. The machine is made of five major parts: the feed hopper (for holding the seeds to be dehulled before getting into the dehulling chamber), dehulling chamber (the part of the machine that impacts forces on seeds thereby causing fractures and opening of seeds coats for the delivery of the oily kernels), discharge unit (exit for oily kernels and seed coats after dehulling), the frame (for structural support and stability of all parts of the machine) and electric motor (power source of the machine).The development process involved design of major components (shaft diameter (20 mm), machine velocity (7.59 m/s), power requirement (3hp single phase electric motor) and structural support of 45???????? × 45???????? × 3????????mild steel angle iron), selection of construction materials and fabrication. ANSYS R14.5 machine design computer software was used to design the shaft and structural support; while other components were designed with conventional design method of using design equations. The machine works on the principle of centrifugal and impact forces. Performance evaluation was carried out after fabrication and 87.26%, 2.83g/s, 8.9% and 3.84%were obtained for dehulling efficiency, throughput capacity, percentage partially dehulled and percentage undehulled respectively